Bibliography of Italian Studies in Poland: Project Description and Statistics - Słapek, Daniel; Biernacka-Licznar, Katarzyna (Quaderni d'Italianistica, 2023)
The aim of the Bibliography of Italian Studies in Poland (BISP) project is to create a complete database of scientific publications written by scholars employed by Italian studies departments of Polish higher education institutions. This article presents a detailed description of the project and the results of a thorough bibliographic analysis of the publications included in BISP, which encompasses texts from three disciplines: linguistics, literary studies, and cultural and religious studies. The analyzed data concern the publications of Italian studies researchers who are currently active at Polish universities: 149 monographs, 113 edited volumes, 1,151 journal articles, and 1,415 chapters in collected monographs—a total of 2,828 publications, written by 145 authors. Our objective is to identify any discernible trends in terms of publishing research results by the analyzed group of researchers.